Sugar cane yield related to the residual nitrogen from fertilization and the root system - Vitti, André Cesar; Trivelin, Paulo Cesar Ocheuze; Gava, Glauber José Castro; Penatti, Claudimir Pedro; Bologna, Isabela Rodrigues; Faroni, Carlos Eduardo; Franco, Henrique Coutinho Junqueira (Pesquisa Agropecuaria Brasileira, 2007)
The work was carried out between two harvesting seasons, without burn, to evaluate the residual effect of the nitrogen fertilization on the 2nd ratoon crop of sugar cane (harvest 1999/2000), and the effect of N and S content in the root system on the following productivity of the next cycle (3rd ratoon crop – harvest 2000/2001). The experiment design was in randomized blocks with six treatments and four replications. The harvest 1999/2000 treatments were 0, 35, 70, 105, 140 and 175 kg ha-1 of N as ammonium nitrate), which was applied over the stove. In the 3rd ratoon crop 100 kg ha-1 of N were applied in all the treatments of the previous harvest season. The first year plots contained microplots, which received the ammonium nitrate labeled with 15N in the ammonium fraction. N doses showed high significant linear effect in the cane production of the 2nd ratoon crop as well as on the next harvest season (3rd ratoon crop) even applied in a unique N dose; nitrogen fertilization and N and S content of the root system were positively related with the sugar cane productivity in the next harvest season.